2014
DOI: 10.1016/j.yhbeh.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the behavioural and hypothalamic–pituitary–adrenal response to contextual fear conditioning in rats

Abstract: SummaryIn recent years, special attention is being paid to sex differences in susceptibility to disease. In this regard, there is evidence that male rats present higher levels of both cued and contextual fear conditioning than females. However, little is known about the concomitant hypothalamicpituitary-adrenal (HPA) axis response to those situations which is critical in emotional memories.Here, we studied the behavioural and HPA responses of male and female Wistar rats to context fear conditioning using elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 89 publications
5
40
2
1
Order By: Relevance
“…It is well established that fear extinction learning and memory is dependent on the phase of the estrus/menstrual cycle in which female rats and humans initially learn extinction (Milad et al 2009;Daviu et al 2014). Consistent with these prior data, we observed that female rats that initially learned fear extinction in proestrus and estrus, phases of the estrus cycle during which levels of estradiol are highest, were protected against fear renewal (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…It is well established that fear extinction learning and memory is dependent on the phase of the estrus/menstrual cycle in which female rats and humans initially learn extinction (Milad et al 2009;Daviu et al 2014). Consistent with these prior data, we observed that female rats that initially learned fear extinction in proestrus and estrus, phases of the estrus cycle during which levels of estradiol are highest, were protected against fear renewal (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, male rats trained to avoid an aversive arm (bright light and loud noise) in a plus maze, made more entries into the arm when the aversive stimuli were no longer present during extinction, while female rats decreased aversive arm exploration, indicating failure to extinguish the behavior (Ribeiro et al, 2010). In a separate study, males performed better in a contextual fear conditioning task, while females expressed less fear and a higher extinction rate than males (Daviu et al, 2014). Baran and colleagues (2009), however, reported that although males and females acquired fear similarly, the female rats did not extinguish as well as males.…”
Section: Sex Differences In Fear Extinctionmentioning
confidence: 87%
“…Some studies report that females do not perform as well as males in fear conditioning and extinction learning (Baker-Andresen, Flavell, Li, & Bredy, 2013; Baran et al, 2009, 2010; Fenton et al, 2014). Male rats exhibit more freezing to the conditioned stimulus in fewer trials during fear conditioning compared to females (Aguilar et al, 2003; Baran et al, 2009, 2010; Daviu, Andero, Armario, & Nadal, 2014; Maren, De Oca, & Fanselow, 1994; Pryce, Lehmann, & Feldon, 1999; Ribeiro et al, 2010). Moreover, male rats trained to avoid an aversive arm (bright light and loud noise) in a plus maze, made more entries into the arm when the aversive stimuli were no longer present during extinction, while female rats decreased aversive arm exploration, indicating failure to extinguish the behavior (Ribeiro et al, 2010).…”
Section: Sex Differences In Fear Extinctionmentioning
confidence: 93%
“…This may indicate that cues related to fear memories are not affected by RP, or that a higher dose of RP is required to be meaningful. Other types of fear-related behaviors, such as rattling, were more frequently observed during the presentation of auditory cues, which may have confounded the results by reducing the freezing time (22). …”
Section: Discussionmentioning
confidence: 99%